PENGARUH MULTIMEDIA INTERAKTIF (BSD MIPA) TERHADAP PEMAHAMAN KONSEP IPA PESERTA DIDIK KELAS VII SMPN 1 GILIRENG KABUPATEN WAJO - Dian Mukarramah (Program Studi Pendidikan Fisika Unpacti Makassar, 2023)
The Influence of Interactive Multimedia on Understanding Science Concepts in Grade VII at SMPN 1 Gilireng in Wajo Regency. Thesis, Physics Education Department, Postgraduate Program, State University of Makassar (supervised by Helmi and Khaeruddin). This study aims to discover whether there is an influence of using interactive multimedia on understanding science concepts. This study is an experimental study with a post test-only control group design. The population consisted of grade VII SMPN 1 Gilireng in the 2021/2022 academic year. Sampling in this study employed purposive sampling technique and obtained grade VII.B as the experimental class with 22 students and grade VII.A as the control class with 22 students. Data on understanding science concepts was collected by employing a test. The results of the research data were analyzed using the SPSS 26.0 statistical test. The results of the study indicate that (1) the understanding science concepts of students in grade VII at SMPN 1 Gilireng taught by using interactive multimedia is in very high category, (2) the understanding science concepts of students in grade VII at SMPN 1 Gilireng taught by using power point media is in high category, and (3) there is a significant influence on the use of interactive multimedia on understanding science concepts of students in grade VII at SMPN 1 Gilireng in Wajo Regency